PENGGUNAAN SUMBER DAYA INFORMASI TERCETAK DAN ELEKTRONIK BERDASARKAN PEKERJAAN ORANG TUA MAHASISWA DI PERPUSTAKAAN UNIVERSITAS SUMATERA UTARA - Hasugian, Jonner (Journal of Documentation and Information Science, 2019)
This study aims to examine the expected satisfaction (gratification sougth) and the obtained satisfaction (gratification obtained) from the use of information resources available at the USU Library. The theoretical model used to study it is the Uses and Gratification theory. The instruments used to collect data were questionnaires that distributed to 391 samples /respondents from 47 Study Program (undergraduate) students (S1) in the USU who often used printed and electronic information resources at the USU Library. Data were analyzed using the SPSS version 17, and Lisrel version 8.8 application program. Analysis data using Chi-Square statistical analysis, multivariate variance analysis (MANOVA) and path analysis. Chi-Square analysis is done to see some use of information resources based on the work of student parents. The results of the study show that: (1) There is a significant difference in the expected satisfaction (gratification sougth) from the use of information resources regarding student parents in the USU Library; (2) There is no significant difference in the use of information resources based on the work of parents of students in the USU Library; (3) There is a trend that students whose parents' work as Police, Employees of BUMN and Civil Servants are more comfortable using electronic information resources than printed; (4) There is no significant difference in obtained satisfaction (gratification obtained) from the use of information resources based on the work of parents of students in the USU Library; (5) The obtained satisfaction by students whose parents' works as Farmers, BUMN Employees, and Police tend to be higher than the obtained satisfaction by students whose parents work as Fishermen, Civil Servants, Private Employees, Teachers, Military and others after using or accessing various types both printed and electronic information resources available at the USU Library; (6) There is no significant discrepancy between the gratification sougth and gratification obtained from the use of information resources based on the work of students? parents at the USU Library.